2010
DOI: 10.1523/jneurosci.2532-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Cortical Activity in the First Two Decades of Life: A High-Density Sleep Electroencephalogram Study

Abstract: Evidence that electroencephalography (EEG) slow-wave activity (SWA) (EEG spectral power in the 1-4.5 Hz band) during non-rapid eye movement sleep (NREM) reflects plastic changes is increasing (Tononi and Cirelli, 2006). Regional assessment of gray matter development from neuroimaging studies reveals a posteroanterior trajectory of cortical maturation in the first three decades of life (Shaw et al., 2008). Our aim was to test whether this regional cortical maturation is reflected in regional changes of sleep SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
401
6
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(453 citation statements)
references
References 66 publications
41
401
6
5
Order By: Relevance
“…Strongest in lower frequencies with t-values up to 10 and higher, the power reduction was similar between EO and EC oscillations. Consistent with other studies (Boord et al, 2007;Kurth et al, 2010), this effect to a lower degree extended also to higher frequencies. According to previous publications, we do not believe that the observed EEG effects are massively influenced by changes of physical properties of the head (e.g., skull conductance or impedance) which change during early development, as these changes appear to be less prominent for the present age range (Hoekema et al, 2003).…”
Section: Brain Development and Eeg Maturationsupporting
confidence: 92%
“…Strongest in lower frequencies with t-values up to 10 and higher, the power reduction was similar between EO and EC oscillations. Consistent with other studies (Boord et al, 2007;Kurth et al, 2010), this effect to a lower degree extended also to higher frequencies. According to previous publications, we do not believe that the observed EEG effects are massively influenced by changes of physical properties of the head (e.g., skull conductance or impedance) which change during early development, as these changes appear to be less prominent for the present age range (Hoekema et al, 2003).…”
Section: Brain Development and Eeg Maturationsupporting
confidence: 92%
“…Less intense waking neuronal activity would decrease the need (substrate) for NREM recuperation, reducing the intensity (power) of the two recuperative frequencies, delta and theta. Further indirect support for this interpretation is provided by topographic differences in the timing of the delta decline (12,13). The age of fastest NREM delta decline shows a back-to-front distribution similar to the back-to-front maturational pattern reported for structural MRI-measured cortical thinning (14).…”
Section: Discussionmentioning
confidence: 65%
“…One emerging area of work that may help shed light on the role of sleep and development is through the examination of slow-wave activity (SWA) as measured by sleep EEG. Two studies have found that the pattern of changes in SWA reflects typical cortical maturation, with a shift from posterior to anterior regions across childhood and adolescence (Kurth et al, 2010(Kurth et al, , 2012. For example, a predominance of SWA in the occipital lobe in early childhood corresponds with the development of visual acuity, whereas a predominance of SWA in the frontal lobes is seen in adolescence, corresponding to the development of executive functioning.…”
Section: Critical Periods Of Development?mentioning
confidence: 99%